2018
DOI: 10.3390/f9080497
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance of Fungi, Bacteria and Denitrification Genes during Insect Outbreaks in Scots Pine Forests

Abstract: Abstract:Outbreaks of defoliating insects may affect microbial populations in forests and thereby mass balances and ecosystem functioning. Here, we investigated the microbial dynamics in Scots pine (Pinus sylvestris L.) forests during outbreaks of the nun moth (Lymantria monacha L.) and the pine-tree lappet (Dendrolimus pini L.). We used real-time PCR (polymerase chain reaction) to quantify genes that characterize bacterial and fungal abundance and the denitrification processes (nirK, nirS, nosZ clades I and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Standard curves for qPCRs were generated in two replicates using 1:3 serial dilutions in 0.5X TE buffer. Standards of Bacterial 16S rRNA, fungal 18S rRNA, nirK , nirS , nosZ clade I and nosZ clade II genes were obtained as described previously [46]. AOA amoA gene was obtained from an environmental clone, cloned in plasmid pGEM-T (Promega, Mannheim, Germany) and multiplied in Escherichia coli JM109.…”
Section: Methodsmentioning
confidence: 99%
“…Standard curves for qPCRs were generated in two replicates using 1:3 serial dilutions in 0.5X TE buffer. Standards of Bacterial 16S rRNA, fungal 18S rRNA, nirK , nirS , nosZ clade I and nosZ clade II genes were obtained as described previously [46]. AOA amoA gene was obtained from an environmental clone, cloned in plasmid pGEM-T (Promega, Mannheim, Germany) and multiplied in Escherichia coli JM109.…”
Section: Methodsmentioning
confidence: 99%
“…The defoliation caused by insect outbreaks has reduced the carbon sequestration in cell walls [33], specific leaf area, and water-use efficiency in trees [34], but has also indirectly affected the physiology of trees by disturbing the nitrogen cycling as well as microbial populations in the forest soil [35,36]. Under water shortage, an increasing vulnerability of trees to insect outbreaks has been observed [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The increased soil C/N ratios of the feces treatment in our incubation experiment may therefore be an indicator of microbial immobilization, and this is supported by the relatively slow decrease of the gas emission rates following peak emissions. In contrast, C/N ratios under field conditions are often observed to decrease during insect outbreaks [20,23,24,40], even on our sampling sites [41].…”
Section: Discussionmentioning
confidence: 57%
“…Further, N 2 O emissions from forest soils are spatial and temporal highly variable ("hot spots" and "hot moments" of N 2 O emissions [48]), which makes measurement and comparability across sites difficult [45]. However, on our infested study site, the abundance of NO 2 reducers (nirK genes) in the soil was also found to be increased [41], indicating a genetic potential for accelerated N 2 O emissions. To our knowledge, we show for the first time that both CO 2 and N 2 O emissions can be triggered simultaneously by organic inputs deriving from pest insects.…”
Section: Discussionmentioning
confidence: 83%